Making occupational health and safety management systems 'work': A realist review of the OHSAS 18001 standard. (September 2020) - Uhrenholdt Madsen, Christian; Kirkegaard, Marie Louise; Dyreborg, Johnny; Hasle, Peter
Highlights: Certified Occupational Health and Safety Management Systems work in specific contexts. COHSMS works through integration, learning, motivation, translation and attention. Organizations thus must assess whether their organization will benefit from COHSMS. Abstract: Certified occupational health and safety management systems (COHSMS) after Occupational Health and Safety Assessment Series (OHSAS) 18001 is now widely applied and the application thereof can be expected to grow considerably, with the publication of the new International Organization for Standardization (ISO) 45001. During the last decade a growing body of research has provided results on many aspects of such management systems, though an overview of the results has so far been lacking. We address this gap in the research with a realist review of the mechanisms of OHS management systems. After a thorough literature search 18 papers with empirical studies qualified for the review. We used a realist synthesis procedure to analyze for program theories and secondly to analyze for context-mechanism-outcome (CMO) configurations. The analysis of the OHSAS 18001 standard shows three program theories: operational, institutional and compliance. Five CMO configurations confirm the program theories: integration, learning, motivation, translation and attention. The configurations emphasize that certain combinations of context and mechanisms are necessary for the successful application of OHS management systems. Therefore, we describe specific paths to the successful implementation of COHSMS as well as the internal contextual elements that must be in place in order to follow them. Our research can thus be used by organizations as the basis for thorough internal evaluations before commencing a certification scheme. More research is needed for a more fine-grained understanding of how to secure a successful outcome and for the function of the new ISO 45001.